Myocardial revascularization in patients with type 2 diabetes mellitus: An overview of modern techniques - Elena Zelikovna Golukhova (Endocrinology Research Centre, 2016)
For patients with coronary artery disease (CAD), in combination with diabetes mellitus, diffuse multivessel coronary artery lesions are common. Such patients are prone to a more rapid progression of atherosclerosis, significantly increasing the need for myocardial revascularization. The choice of an optimal approach determines the prognosis and course of CAD. The results of randomized trials show that the use of percutaneous coronary interventions with drug-eluting stents is appropriate for patients with one or two coronary artery lesions, but that coronary artery bypass graft surgery is preferred in cases of multivessel disease and significantly reduces the risk of long-term adverse events. It should also be noted that the use of modern generations of stents allows the achievement of comparable results in terms of long-term mortality, which was most convincingly demonstrated in patients with one or two vascular lesions.